The salt industry in Kansas - Dern, Harry Leroy (My University, 1900)
Introduction: Salt is one of most useful minerals that is produced from the bowels of the earth. It is indispensable to us as an appetizer, and for preserving meat, and from Biblical times down to the present it has been in constant demand. In the first books of the Old Testament, we find salt spoken of, and we have records of its being manufactured by mechanical means before the birth of Christ. In America, the Jesuit missionaries found salt springs while among the Indians, and as early as the middle of the seventeenth century, salt was manufactured by the Indians in New York. It was not until 1878 that rock salt was discovered in New York, and ten years later, inexhaustible beds were found in Kansas, Michigan, Louisiana, Utah, and other states. The salt in Kansas occurs in two relatively distinct forms: (1) That left in the salt marshes when the evaporation takes place during dry seasons; and second, rock salt, found beneath the surface. The area containing salt marshes reaches from Republic county to Barber county. Rock salt is know to exist under an area comprising several counties in the south central part of the state. (See Plate II). Salt was collected from the marshes as early as 1861, but Kansas was not counted with the salt producing states until rock salt was discovered in 1888. Two kinds of salt are sent out from the factories; (1), Rock salt, in which the solid rock is blasted, brought to the surface, crushed, screened, and put on the market; and (2), evaporated salt, in which brine is evaporated in large pans or vats, leaving the crystalized salt ready for the market.
Citation: Dern, Harry Leroy. The salt industry in Kansas. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Salt; Rock Salt; Minerals; Kansas; Theses